Assistance for parents with unsettled infants in Central Vietnam: a qualitative investigation of health professionals' perspectives - Linda Murray; Thach Tran; Vo Van Thang; Nicole McDonald; Sean Beggs; Jane Fisher (BMC, 2019)
Abstract Background Unsettled infant behaviours are a common concern for parents internationally, and have been associated with maternal stress, reduced parenting confidence, and postnatal mental health problems among parents. Little information currently exists regarding available support for the parents of unsettled infants in low-and-middle income countries such as Vietnam. We aimed to describe how unsettled infant behaviour was understood and investigated by Vietnamese health professionals, and what health education was provided to parents regarding infant sleep and settling. Methods This qualitative study elicited the perspectives of Vietnamese health professionals working in Thua Thien Hue Province, Vietnam. A semi-structured interview guide included participant demographics, and questions about providing assistance to the parents of unsettled infants, understandings of unsettled infant behaviour, management of unsettled infant behaviour and health education. Individual interviews or small-group discussions were undertaken in Vietnamese, data were translated and analysed in English. The authors used a thematic approach to analysis, supported by Nvivo software. Results Nine health professionals (four primary care doctors, one paediatrician and four nurses/midwives) working in urban and rural areas of Thua Thien Hue were interviewed. Four themes were created that reflected the responses to the literature-based interview questions. Health professionals described having received little formal training about infant sleep and settling, thus based their advice on personal experience. Information on infant sleep and settling was not included in health education for new mothers, which focused on breastfeeding and preventing malnutrition. Where advice was given, it was generally based on settling strategies involving high levels of caregiver intervention (holding, rocking, breastfeeding on demand and tolerating frequent overnight wakings) rather than behaviour management style strategies. Participants emphasised the importance of recognising and responding to infant behavioural cues (e.g infants cry when hungry). Conclusions There is an unmet need for information on infant sleep and settling for new parents and health professionals in Vietnam. Our findings suggest information for caregivers on how to respond sensitively to infant tired signs should be formally included in the training of health professionals in LALMI settings. Sleep and settling information should also be part of culturally appropriate multi-component maternal and child health interventions aimed at promoting early childhood development.